SIGNIFICANCE OF URINARY AMINOPEPTIDASE N AND DIPEPTIDYL PEPTIDASE IV IN EARLY DIAGNOSIS OF KIDNEY DAMAGE IN CHILDREN WITH TYPE 1 DIABETES MELLITUS IN NORTH-EASTERN REGION OF UKRAINE - Vikhrova, Iryna; Loboda, Andrii; Zmyslia, Igor (Eastern Ukrainian Medical Journal, 2024)
Introduction. Compared to adults, diabetes in children and adolescents follows a more aggressive clinical course. This is characterized by a reduced response to current treatments, a faster decline in β-cell function, the rapid progression of insulin resistance, and an accelerated development of both microvascular and macrovascular complications. Diabetic nephropathy stands out as one of the most critical and common complications of diabetes and is the leading cause of end-stage renal disease. This makes type 1 diabetes mellitus particularly significant for pediatric nephrologists. While clinical signs of diabetic nephropathy, such as albuminuria and a decline in glomerular filtration rate, typically manifest over a longer period (10–25 years), specific structural changes in the kidneys, such as glomerular basement membrane thickening and mesangial expansion can occur much earlier, within 1.5 to 5 years of diabetes onset. Notably, diabetic nephropathy affects not only the glomeruli but also involves tubular damage. Tubulointerstitial lesions often precede glomerular injury, suggesting that tubular biomarkers might be more sensitive for early detection. Markers with peptidase activity have proven effective in identifying early tubular injury. Aminopeptidase N, an ectopeptidase widely expressed in the kidneys, is a recognized urinary marker for proximal tubule damage. Similarly, Dipeptidyl peptidase IV is expressed in glomerular visceral epithelial cells, endothelial cells, and the brush border of proximal tubules. Elevated urinary Dipeptidyl peptidase IV levels have been detected in diabetic patients with normoalbuminuria, indicating its potential as an early biomarker for the onset of diabetic nephropathy.Objective. To determine urinary Aminopeptidase N and Dipeptidyl peptidase IV levels in children from north-eastern region of Ukraine depending on the diabetes duration.Materials and methods. A total of 55 participants were included in the study, comprising 47 children with type 1 diabetes mellitus and 8 children with no history of diabetes and kidney disease. The patients with type 1 diabetes mellitus were divided into three groups based on disease duration: less than 1 year (11 participants), 1–5 years (24 participants), and more than 5 years (12 participants). The chemiluminescence signals of Aminopeptidase N and Dipeptidyl peptidase IV in urine were analyzed using the Proteome Profiler Human Kidney Biomarker Antibody Array (R&D Systems, Minneapolis, USA) and the Bio-Rad ChemiDoc Touch imaging system. Statistical analysis was conducted using descriptive statistics and nonparametric methods, including contingency tables and Spearman’s rank correlation coefficient (r). Results with p < 0.05 were considered statistically significant.Results. Urinary Aminopeptidase N and Dipeptidyl peptidase IV levels statistically increased in children with the duration of type 1 diabetes mellitus less than one year. Aminopeptidase N showed moderate correlation with glomerular filtration rate (r=0.589, p=0.044). While Dipeptidyl peptidase IV was strongly positive correlated with glomerular filtration rate (r=0.869, p=0.0001) and weaker correlation with Aminopeptidase N (r=0.467, p=0.126).Conclusions. Serum creatinine levels rise significantly only 1–5 years after the onset of type 1 diabetes mellitus, making it unsuitable as an early predictor of kidney damage in children with type 1 diabetes mellitus. Both Aminopeptidase N and Dipeptidyl peptidase IV are reliable markers for the early detection of renal injury in children with type 1 diabetes mellitus in north-eastern region of Ukraine. Among these, Dipeptidyl peptidase IV is a preferable non-invasive marker for early kidney damage due to its specific localization in the proximal tubules and glomerular epithelium, as well as its strong positive correlation with glomerular filtration rate.